Modulating microbiome-immune axis in the deployment-related chronic diseases of Veterans: report of an expert meeting - Jun Sun; M. Nedim Ince; Clara Abraham; Terrence Barrett; Lisa A. Brenner; Yingzi Cong; Reza Dashti; Pradeep K. Dudeja; David Elliott; Thomas S. Griffith; Peter S. Heeger; Andrew Hoisington; et al. (Gut Microbes, 2023)
ABSTRACTThe present report summarizes the United States Department of Veterans Affairs (VA) field-based meeting titled “Modulating microbiome-immune axis in the deployment-related chronic diseases of Veterans.” Our Veteran patient population experiences a high incidence of service-related chronic physical and mental health problems, such as infection, irritable bowel syndrome (IBS), inflammatory bowel disease (IBD), various forms of hematological and non-hematological malignancies, neurologic conditions, end-stage organ failure, requiring transplantation, and posttraumatic stress disorder (PTSD). We report the views of a group of scientists who focus on the current state of scientific knowledge elucidating the mechanisms underlying the aforementioned disorders, novel therapeutic targets, and development of new approaches for clinical intervention. In conclusion, we dovetailed on four research areas of interest: 1) microbiome interaction with immune cells after hematopoietic cell and/or solid organ transplantation, graft-versus-host disease (GVHD) and graft rejection, 2) intestinal inflammation and its modification in IBD and cancer, 3) microbiome-neuron-immunity interplay in mental and physical health, and 4) microbiome-micronutrient-immune interactions during homeostasis and infectious diseases. At this VA field-based meeting, we proposed to explore a multi-disciplinary, multi-institutional, collaborative strategy to initiate a roadmap, specifically focusing on host microbiome-immune interactions among those with service-related chronic diseases to potentially identify novel and translatable therapeutic targets.